Workers, Managers, and Customers: Triangles of Power in Work Communities - Lopez, Steven Henry (Work and occupations, 2010)
The sociology of service work has blossomed in the 10 years since Work and Occupations first published a special issue on this subject. This introductory essay chronicles developments and new debates around emotional labor, worker–customer relationships in the service triangle, and the nexus of gender and control in service work. Several neglected themes are highlighted, including the relationship between race and the organization of work on the shop floor, as well as a number of themes that were once prominent in industrial sociology but which have fallen into relative neglect in the sociology of service work despite their continuing relevance.